Sining biswal a documentary on Philippine visual arts (Manila Cultural Center of the Philippines, 1989)
Traces the history of Philippine art from pre-hispanic to modern times.
VHS format.
Direction, Lito Tiongson ; script, Alice G. Guillermo.
Narration, Leandro V. Locsin.
Keywords: Art -- Philippines -- History